2022
DOI: 10.1108/jeas-02-2022-0050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustainable supply chain management on cost performance: empirical evidence from manufacturing companies of Bangladesh

Abstract: PurposeThe aim of the study has been performed to investigate the relationship between sustainable supply chain management (SSCM) practices and the cost performance of manufacturing firms in Bangladesh. Moreover, this paper highlights the key environment-friendly approaches and their association with financial performance in Bangladesh.Design/methodology/approachThe paper empirically assesses sustainable supply chain performance using four major supply chain practices, including sustainable procurement, sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…Therefore, the specified hypothesis (null) was renounced, hence, it suggested that physical environment had a meaningful influence on employees' effectiveness in Colman Technical Industries Ltd, Arepo. This result validated the Khawar and Aqeel (2017)'s study that established a positive effect of physical environment on the effectiveness of workers in the manufacturing industry of Lahore, Pakistan. H02: There is no significant impact of job safety and security on the employee's creativity in the study area.…”
Section: The Testing Of the Study's Hypothesessupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, the specified hypothesis (null) was renounced, hence, it suggested that physical environment had a meaningful influence on employees' effectiveness in Colman Technical Industries Ltd, Arepo. This result validated the Khawar and Aqeel (2017)'s study that established a positive effect of physical environment on the effectiveness of workers in the manufacturing industry of Lahore, Pakistan. H02: There is no significant impact of job safety and security on the employee's creativity in the study area.…”
Section: The Testing Of the Study's Hypothesessupporting
confidence: 84%
“…The result of the research therefore indicated a meaningful link amid work environmental factors and performance of employees. Also, Khawar and Aqeel (2017) examined the influence of environment factors on performance of 352 respondents in the manufacturing industry of Lahore. The study therefore used correlation and regression to test its hypotheses, while the results established positive influence of work environment on the employees' performance in the studied industry.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Sustainable performance does not affect cost performance. To follow the law of procurement, it can be used as a guideline to make supply chain policies in the least developed countries [15]. The traditional supply chain was cost reduction-centric; however, the long supply chain is focused on the right time delivery ensuring the quality of the product [16].…”
Section: A New Era Of Global Supply Chain Management and Traditional ...mentioning
confidence: 99%
“…A study discovered on cost performance research that a sustainable supply chain is positively supported by two variables: sustainable procurement and investment recovery [15]. However, on the other hand, it is negatively influenced by cost performance.…”
Section: Sustainable Supply Chain Managementmentioning
confidence: 99%